No country for righteous men and other essays in a culture of offendedness - Thayaparan, S. (Strategic Information and Research Development Centre, 2014)
No Country for Righteous Men is a collection of essays that examines the political landscape of Malaysia after five decades of independence. Although the writer claims partisanship to a specific political alliance, it is by no means a polemical work against the UMNO Establishment. What these essays attempt to do, is navigate through partisan terrain in the hopes of establishing a safe secular route out of this political quagmire of race and religious politics. Using contemporary highly politicized issues as a launching pad to discover themes purposely hidden by the rhetoric of stability or change, this book offers an alternative view of what those who want to remain in power or those who want to claim power, gloss over in their quest for political hegemony. These essays are a reminder that principle and real politick are mutually exclusive and the price of adhering to principle means sometimes losing populist appeal. It is a record of a period that nearly brought the Opposition alliance to Federal power but more importantly, it is a chronicle of the author's search for meaning, in an era of slogans and political bromides meant to appease the voting Malaysian public.